Development of Interactive Multimedia Integrating the Love-Based Curriculum for Tajwid Instruction in the Al-Qur'an Hadith Subject for Grade VIII Students at Islamic Junior High School - Jihan Syahrani; Septriyan Anugrah; Alkadri Masnur; Elsa Masriani (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The teaching of Qur’an–Hadith, particularly tajwid for eighth-grade Islamic junior high school students, continues to face challenges arising from reliance on conventional instructional materials, limited use of technology-enhanced learning media, and the suboptimal integration of the Love-Based Curriculum (Kurikulum Berbasis Cinta; KBC), which may reduce students’ motivation and learning outcomes. This study aimed to develop an interactive multimedia application integrating KBC values into tajwid instruction and to evaluate its validity, practicality, and effectiveness. A Research and Development approach was employed using the 4-D model, comprising Define, Design, Develop, and Disseminate stages. The multimedia application was developed using Articulate Storyline and tested with eighth-grade students at MTs Negeri 11 Agam. Product quality was assessed through expert validation, practicality testing, and effectiveness testing using N-Gain analysis. The findings demonstrated that the developed multimedia satisfied the criteria for validity, practicality, and effectiveness, indicating its feasibility for classroom implementation. The application integrates text, images, audio, video, animation, and interactive exercises with the Five Pillars of Love promoted within KBC, thereby facilitating a more engaging and meaningful learning experience. Its implementation also improved students’ learning outcomes, as indicated by the effectiveness test. The study concludes that the developed interactive multimedia is suitable for supporting tajwid instruction in eighth-grade Qur’an–Hadith classes. This study contributes an innovative instructional medium that enables teachers to integrate educational technology with character education, thereby strengthening student engagement and enhancing the quality and effectiveness of the learning process.